DIFFERENT DILUTIONS AND USE OF RECYCLE IN THE ANAEROBIC BIODIGESTION OF CRUSHED AND SIEVED POULTRY LITTER: BATCH TEST - Sagula, A.L.; da Costa, L.V.C.; de Lucas Junior, J. (Revista Brasileira de Engenharia de Biossistemas, 2017)
The poultry litter generated in the production process bird shows great potential for obtaining energy using biodigesters, but it is necessary and it is able to facilitate the process and separation of solids. The objective of the work was to produce biogas in the process of biodigestion, with different solutions, with a 20% use of recycle in a batch supply system. Twenty-four batch digesters were used, with a capacity of 2L of substrate in fermentation. The equipment used for processing the chicken litter was a crusher pump that homogenizes and crushes the chicken litter into smaller particles to facilitate and improve efficiency in biodigestion. For a separation of the solid fraction for a 1mm mesh vibrating screen. Dilutions 1: 8, 1:10 and 1:12 and 20% recycle (biofertilizer) were studied in substitution of water. The treatment of poultry litter in a dilution of 1: 8 showed the greatest reduction in volatile solids (72.76%) compared to other treatments. The treatment with recycle at the 1: 8 dilution was the one with the highest biogas production with an average value of 0.0328 m3, in relation to the other treatments. It is concluded that the use of the recycle does not interfere in the production of biogas and there was an increase in the production.